1979
DOI: 10.1111/j.1471-4159.1979.tb09918.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of High Affinity Glutamic Acid Transport by Rat Cortical Synaptosomes–a Refinement of the Originally Proposed Model

Abstract: Abstract– In a previous publication (Wheeler & Hollingsworth, 1978), a model was presented which accounted for the role of sodium in the high affinity transport of glutamic acid in rat brain synaptosomes. Subsequent studies confirmed a lack of fit of the model to the data at the higher sodium and glutamate concentrations. The model has therefore been reexamined and refined. By removing some of the restrictions placed on the original model, a model emerges which fits the data at all sodium and glutamate concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Lineweaver-Burk plots at each of the sodi um concentrations used (except for [Na] = 0) are linear (25,28). Both the intercept and tire slopes of the lines change with [Na], Thus, both Va and Kt are functions of the [Na].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lineweaver-Burk plots at each of the sodi um concentrations used (except for [Na] = 0) are linear (25,28). Both the intercept and tire slopes of the lines change with [Na], Thus, both Va and Kt are functions of the [Na].…”
mentioning
confidence: 99%
“…Numerous simplifications of the above model were fitted to the data (25,28). For glutamic acid, dropping any part of the model resulted in a substantially higher error in the model fit.…”
Section: Minimal Best Fit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…When [Na+]i is high, on the other hand, the carrier will stay longer in the state where it can rebind glutamate (because Na+ can rebind before the carrier conformation changes to one that cannot rebind Na+ or glutamate), and raising the intracellular glutamate concentration will inhibit uptake. Similarly, Wheeler (1979) concluded that, at the external face, at least some of the sodium binds before glutamate. Kanner & Bendahan (1982) propose a reaction scheme similar to that shown in Fig.…”
mentioning
confidence: 99%
“…Transport processes play a critical role in the synaptic function of the putative amino acid neurotransmitters, since they are necessary for inactivation of transmitter following stimulus-induced release (Krnjevic, 1974;Roberts et al, 1976). Extensive kinetic studies of the high affinity transport of GABA and glutamic acid in rat brain synaptosomes have been carried out in this laboratory (Wheeler, 1979(Wheeler, a, b, 1981Hollingsworth, 1978, 1979;Wheeler, Wise, and Callihan, 1980). Initial velocity of uptake has been measured as a function of both sodium and amino acid concentration, and computer optimization techniques used to fit these data to each of several plausible models.…”
Section: Introductionmentioning
confidence: 98%